If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6xn + -9 = -15 Reorder the terms: -9 + 6nx = -15 Solving -9 + 6nx = -15 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 6nx = -15 + 9 Combine like terms: -9 + 9 = 0 0 + 6nx = -15 + 9 6nx = -15 + 9 Combine like terms: -15 + 9 = -6 6nx = -6 Divide each side by '6x'. n = -1x-1 Simplifying n = -1x-1
| 1024+4x=12 | | 4(x-1)-(2-x)=5(x-2)+4 | | -x-4(0)=6 | | -x+2=3x+4x | | -15=3x+6 | | 7/5x+8/3x | | 5x-12x=56 | | 7c-9=9(2c-8)+4c | | B+3.5B=81 | | 8+2t+2=2(t+5) | | 3x-2+x+8=2(3x+7-x-4) | | 2a+1=16 | | 6-x=32 | | 2x*15= | | 5-x+3x=17 | | -3+2x=2x-3 | | 22=a+2d | | 6-5x-x=66 | | -3(0)+2y=9 | | 584=348 | | s-q=p | | -2n=-3n+6 | | -16+x=7 | | 216/18 | | -14n+12=-10n-16 | | 4(c-8)=3(5+c) | | x/5=0 | | -15=6+X | | 0.5(2x-8)=7x+10 | | 18=2x+4x | | 1/2g=31/3 | | x-100/5.3 |